Fog signaling has diverse roles in epithelial morphogenesis in insects - Matthew Alan Benton; Nadine Frey; Rodrigo Nunes da Fonseca; Cornelia von Levetzow; Dominik Stappert; Muhammad Salim Hakeemi; Kai H Conrads; Matthias Pechmann; Kristen A Panfilio; Jeremy A Lynch; Siegfried Roth (eLife, 2019)
The Drosophila Fog pathway represents one of the best-understood signaling cascades controlling epithelial morphogenesis. During gastrulation, Fog induces apical cell constrictions that drive the invagination of mesoderm and posterior gut primordia. The cellular mechanisms underlying primordia internalization vary greatly among insects and recent work has suggested that Fog signaling is specific to the fast mode of gastrulation found in some flies. On the contrary, here we show in the beetle Tribolium, whose development is broadly representative for insects, that Fog has multiple morphogenetic functions. It modulates mesoderm internalization and controls a massive posterior infolding involved in gut and extraembryonic development. In addition, Fog signaling affects blastoderm cellularization, primordial germ cell positioning, and cuboidal-to-squamous cell shape transitions in the extraembryonic serosa. Comparative analyses with two other distantly related insect species reveals that Fog’s role during cellularization is widely conserved and therefore might represent the ancestral function of the pathway.